2016
DOI: 10.1371/journal.pone.0151801
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin from Shrimp Litopenaeus vannamei Has Antiproliferative Effect against HeLa Cell In Vitro

Abstract: Hemocyanin (HMC) has been shown to participate in multiple roles of immune defence. In this study, we investigated the antiproliferative effect and underpinning mechanism of HMC from Litopenaeus vannamei in vitro. Sulforhodamine B (SRB) assay indicated that HMC could dramatically inhibit the growth of HeLa cells, but not 293T cells under the same conditions. Moreover, typical morphological features of apoptosis in HeLa cells including the formation of apoptotic body-like vesicles, chromatin condensation and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Chang et al (2007) stated that two hours after dopamine injection in dosage 10 -6 , 10 -7 , and 10 -8 mol, the oxyhemocyanin decreased significantly. Oxyhemocyanin is a blue pigment formed by the oxygen and hemocyanin in ratio 1:2 (Cheng et al, 2013), while hemocyanin is a glycoprotein contained copper and it is usually found in the hemolymph (Zheng et al, 2016). The declined oxyhemocynanin disrupted the metabolism, osmoregulation, and resporation system which later caused stress and unable to adapt to the environment (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (2007) stated that two hours after dopamine injection in dosage 10 -6 , 10 -7 , and 10 -8 mol, the oxyhemocyanin decreased significantly. Oxyhemocyanin is a blue pigment formed by the oxygen and hemocyanin in ratio 1:2 (Cheng et al, 2013), while hemocyanin is a glycoprotein contained copper and it is usually found in the hemolymph (Zheng et al, 2016). The declined oxyhemocynanin disrupted the metabolism, osmoregulation, and resporation system which later caused stress and unable to adapt to the environment (Chang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Concholepas concholepas hemocyanin (CCH) from the Loco or Chilean abalone and Fissurella latimarginata hemocyanin (FLH) from the Lapa negra possess immunostimulatory properties such as antitumor activity [11], while Stenzl [20] showed that the functional unit (FU) RvH1-c of hemocyanin from R. venosa possessed strong anticancer activities against bladder cancer permanent cells. Furthermore, our previous studies revealed that hemocyanin of L. vannamei attenuated the proliferation of HeLa cells by modulating the mitochondrial pathway apoptosis as well as exerted a significant antitumor effect on Sarcoma-180 (S180) tumor-bearing mice by enhancing the immunity and antioxidative potential of the mice [12,21]. Besides this, our earlier studies suggested that L. vannamei hemocyanin could react with human IgM, IgG, or IgA as an antigen [22][23][24], bind to bacteria and animal erythrocytes as an agglutinin and hemolysin [23,25] as well as act as an immune-enhancing protein [26].…”
Section: Litopenaeus Vannameimentioning
confidence: 99%
“…Furthermore, our previous studies revealed that hemocyanin of L . vannamei attenuated the proliferation of HeLa cells by modulating the mitochondrial pathway apoptosis as well as exerted a significant antitumor effect on Sarcoma‐180 (S180) tumor‐bearing mice by enhancing the immunity and antioxidative potential of the mice . Besides this, our earlier studies suggested that L .…”
mentioning
confidence: 97%
“…It was hypothesized that the haemocyanin may be redirected to other tissues for shrimp survival (Cimino, Owens, Bromage, & Anderson, ). Recently, purified haemocyanin from L. vannamei was shown to have an antiproliferative effect on HeLa cells via the apoptosis mechanism involving the mitochondria‐triggered pathway (Zheng et al., ).…”
Section: Introductionmentioning
confidence: 99%